Author Correction: Atmospheric mountain wave generation on Venus and its influence on the solid planet's rotation rate. Issue 12 (December 2018) - Navarro, T.; Schubert, G.; Lebonnois, S.
In the version of this Article originally published, a statement regarding past measurements of the length of day and rotation rate of Venus was potentially misleading. The original statement has now been replaced in the online versions of this Article, to acknowledge that neither Magellan nor Venus Express measured an instantaneous rotation rate.